EFFECT OF AUDIT COMPLIANCE PARAMETERS ON REGULATORY FILING TIMELINESS OF SOME SELECTED LISTED COMPANIES IN NIGERIA - Maarufah Abdulmalik Mohammed, Ph.D; Samira MohammedAdimoha, Ph.D; Musa Abubakar Abdullahi Faragai; Abdulkarim Musa Mohammed, Ph.D (Gusau Journal of Accounting and Finance)
The study examines the effect of audit compliance parameters on the regulatory filing timeliness of some selected listed companies in Nigeria. Regulatory filing timeliness is measured by the number of days between the financial year-end and the date the auditor signs the financial statements, while audit compliance parameters are represented by audit firm size, audit tenure, and audit committee size. Using a panel dataset of 42 firms over ten years (2012-2021), comprising 420 firm-year observations, the study employs a descriptive and correlational research design. Secondary data were collected using a convenience sampling approach and analyzed using Feasible Generalized Least Squares (FGLS) regression. The hypotheses tested explore the relationship between each audit compliance parameter and regulatory filing timeliness. The findings show that audit firm size, audit tenure, and audit committee size all have a positive and statistically significant effect on the regulatory filing timeliness of listed firms in Nigeria. The results of the study suggested that larger audit firms, longer audit tenures, and effective audit committees contribute to timely financial disclosures. The study recommends that firms engage reputable auditors, maintain stable auditor relationships, and strengthen auditcommittee composition to enhance timeliness in financial reporting.